LISTENING PROBLEMS FOR JUNIOR HIGH SCHOOL - UCI NURSANTY HALOHO; FERI ANTONI SINAGA; MARIA PAULINA ANGLE RAJAGUKGUK; NADIA JULYANTI NAINGGOLAN; SELVIANA NAPITUPULU (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2022)
The purpose of this research is to obtain descriptive information about problems and problems solving in learning listening comprehension. Researchers use qualitative descriptive research and investigate students' problems in listening comprehension in grade VIII and steps to solve their problem. This sample uses a qualitative descriptive method and is carried out in Kalam Kudus Christian Middle School Pematangsiantar, North Sumatra. The researcher found that the most common problem faced by the four students was lack of concentration, native the speaker's speaking speed, foreign words, and lack of effort to understand each word. The solutions offered to overcome these problems are focus and concentration while listening to class, concentrate on what is heard, and write down the things that are important when listening to the material spoken by a native speaker; find the meaning of a foreign word, look at the dictionary to find it out difficult words, check words that are not clearly heard in the dictionary, memorize vocabulary, and read English text and listen to English audio; and familiarize students with rulers pronunciation to help them hear different forms of fast natural speech and ask them questions imitating the pronunciation of native speakers. It concludes that studying information about problems and problem solving in junior high school is because they learn the results are still far from standard. Therefore, problem solving in listening Understanding of learning is expected to minimize the problems faced by junior high school students in the learning process so that they get satisfactory learning outcomes.